2017
DOI: 10.1371/journal.pone.0183499
|View full text |Cite
|
Sign up to set email alerts
|

Estimating future temperature maxima in lakes across the United States using a surrogate modeling approach

Abstract: A warming climate increases thermal inputs to lakes with potential implications for water quality and aquatic ecosystems. In a previous study, we used a dynamic water column temperature and mixing simulation model to simulate chronic (7-day average) maximum temperatures under a range of potential future climate projections at selected sites representative of different U.S. regions. Here, to extend results to lakes where dynamic models have not been developed, we apply a novel machine learning approach that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Rising temperatures of shallow lentic systems (Butcher et al 2017) can have direct impacts on species if temperatures are already near critical thermal maxima, as well as indirect effects resulting from shifts in water quality and resources (Komatsu et al 2007, Dallas and Rivers‐Moore 2012). Oxygen is less soluble in warmer waters, which can change species interactions and the resulting food web, as many gilled organisms are unable to persist (Verberk and Bilton 2013), creating additional habitat space for species that typically avoid habitats with gilled predators such as fish and amphibian larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Rising temperatures of shallow lentic systems (Butcher et al 2017) can have direct impacts on species if temperatures are already near critical thermal maxima, as well as indirect effects resulting from shifts in water quality and resources (Komatsu et al 2007, Dallas and Rivers‐Moore 2012). Oxygen is less soluble in warmer waters, which can change species interactions and the resulting food web, as many gilled organisms are unable to persist (Verberk and Bilton 2013), creating additional habitat space for species that typically avoid habitats with gilled predators such as fish and amphibian larvae.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the physiological basis of effects on fish by climate change is provided by Whitney et al (2016). Sharma et al (2007) predicted an increase of maximum summer temperatures for lakes in Canada until 2100 and Butcher et al (2017) for lakes in the United States. Many lakes may experience water temperatures as high as 30°C, with Neusiedler See already exceeding that in several years.…”
Section: Potential Biological Impactsmentioning
confidence: 99%
“…Many lakes may experience water temperatures as high as 30°C, with Neusiedler See already exceeding that in several years. Simulated 7-day average maximum water temperatures of more than 30°C are projected to increase from less than 2% to approximately 22% by the end of the twenty-first century (Butcher et al 2017). Consequently, thermal habitats will be altered potentially expanding the range of warm water fish species negatively impacting native cold water fish communities.…”
Section: Potential Biological Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metamodeling methods are used widely across different fields of science and engineering, for example, to optimize designs of coronary stents, 12 high-speed trains, 13 and groundwater remediation, 14 as well as to estimate future water temperatures. 15 In health economics, de Carvalho et al 16 recently demonstrated that a metamodel can be used to perform probabilistic analysis, which was not possible in a feasible time frame using their original model. 16 A previous literature review identified only 13 additional applications of metamodeling methods in health economics, mostly aiming to perform value of information analysis and applying various, relatively basic metamodeling methods compared with those used in other fields of research, suggesting the field of metamodeling within health economics to be in its infancy.…”
mentioning
confidence: 99%